Gamma Rays Effects on the Optical Properties of Cerium‐Doped Glasses. (31st July 2015) - Baccaro, Stefania; Cemmi, Alessia; Di Sarcina, Ilaria; Menchini, Francesca
<x xml:space="preserve">Abstract</x> Optical systems employed in high‐energy environments are subjected to high doses of ionizing radiation and the stability of their optical properties is required to avoid a possible failure of the experiments. Radiation hard glasses are widely used as substrates or windows in high‐energy applications, due to their resistance in hostile environments where energetic particles and γ rays are present. In this work, radiation‐resistant commercial glass samples were irradiated by 60Co γ rays from 50 to 3 × 105 Gy absorbed doses and at three different dose rates. The optical properties of the samples were measured to evaluate the gamma irradiation effects and the damage recovery after the end of irradiation. A dependence on the irradiation dose rates was found.